Characterization of terpene biosynthesis in Melaleuca quinquenervia and ecological consequences of terpene accumulation during myrtle rust infection. Issue 4 (24th June 2021) - Hsieh, Ji‐Fan; Krause, Sandra T.; Kainer, David; Degenhardt, Jörg; Foley, William J.; Külheim, Carsten
Abstract: Plants use a wide array of secondary metabolites including terpenes as defense against herbivore and pathogen attack, which can be constitutively expressed or induced. Here, we investigated aspects of the chemical and molecular basis of resistance against the exotic rust fungus Austropuccinia psidii in Melaleuca quinquenervia, with a focus on terpenes. Foliar terpenes of resistant and susceptible plants were quantified, and we assessed whether chemotypic variation contributed to resistance to infection by A. psidii . We found that chemotypes did not contribute to the resistance and susceptibility of M. quinquenervia . However, in one of the chemotypes (Chemotype 2), susceptible plants showed higher concentrations of several terpenes including α‐pinene, limonene, 1, 8‐cineole, and viridiflorol compared with resistant plants. Transcriptome profiling of these plants showed that several TPS genes were strongly induced in response to infection by A. psidii . Functional characterization of these TPS showed them to be mono‐ and sesquiterpene synthases producing compounds including 1, 8‐cineole, β‐caryophyllene, viridiflorol and nerolidol. The expression of these TPS genes correlated with metabolite data in a susceptible plant. These results suggest the complexity of resistance mechanism regulated by M . quinquenervia and that modulation of terpenes may be one of the components that contribute to resistance against A. psidii .